(untitled) (Historia, 2021)
Commemoration has been, and still is, one of the many successful sculpting tools in the kit of identity carving. Across disciplines it is held that the most important, and one might add the most effective, strategy "as regards the construction of national identity, [is] undoubtedly commemorative practices." Described as "powerful performative devices which contribute to the collective imagination of the past", they take on a range of forms including regular festivities, occasional ceremonies, exhibitions and monuments, as well as commemorative publications, celebratory speeches and creative productions. They are at the most essential level an endeavour to preserve in memory through some form of celebration. The national - or collective - memory upon which these commemorative practices are generally based are held to be "shared by people who ... regard themselves as having a common history". However, the "official" national or state commemoration is generally orchestrated by and conforms to the dominant political or ideological interests as "collective representations" that were designed to give legitimacy to the "elites that represent them". They look to the past and select milestones that buttress a desired present position of power or current ideological dispensation. These commemorations are often imposed by those in authority and very often take on the form of orchestrated propaganda. This accords with the idea that even "History writing is an important part of a nation state’s collective memory and history is not simply a product of the past, but often an answer to the demands of the present".